Investigation of electrical and optical properties of dielectric barrier discharge - Усенов, Е.А.; Габдуллин, М.Т.; Досболаев, M.K.; Данияров, Т.Т.; Рамазанов, T.С. (Recent Contributions to Physics, 2016)
In this paper the results of optical and electrical characteristics of dielectric barrier discharge are presented where were used plane to plane and pin to plane electrode configurations. The dynamic current-voltage characteristics of discharge at different electrode configurations were investigated. The plasma spectrum of air of dielectric barrier discharge was obtained by optical emission spectroscopy method. The results of measurement of the discharge current showed that the barrier discharge generated in the streamer mode and used pin electrode reduces the streamer channels and micro discharges. The plasma spectrum of air showed active components and radicals which can be used for treatment of living tissues and materials.